2016
DOI: 10.3329/seajph.v5i2.28315
|View full text |Cite
|
Sign up to set email alerts
|

Treatment seeking behavior for sexually transmitted infections/reproductive tract infections among married women in urban slums of Mumbai, India

Abstract: Sexually Transmitted Infections/Reproductive Tract Infections (STIs/RTIs) are a major public health problem and a leading cause of morbidity among men and women in developing countries. The aim of the study is to explore treatment seeking behavior among the married women of reproductive age presented with symptoms of STI/RTI. A hospital-based observational study was carried out at the STI/RTI Clinic of Urban Health Centre, Shivaji Nagar, Govandi, Mumbai, India. The study involved a total of 273 married females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(6 reference statements)
1
2
0
3
Order By: Relevance
“…They also concluded that there is no association between the prevalence of infection, religion, and the type of family. [ 13 ] In a study done among the tribal women of Himachal Pradesh, India Knowledge, care seeking and prevalence of RTI, revealed the prevalence of infection to be 22.7% with the presenting complaint of lower abdominal pain with 37.10% followed by vaginal discharge 31.6%, 40% of the affected women seeked treatment. [ 14 ] In the study conducted among the rural women in Telangana by P. Mani.…”
Section: Discussionmentioning
confidence: 99%
“…They also concluded that there is no association between the prevalence of infection, religion, and the type of family. [ 13 ] In a study done among the tribal women of Himachal Pradesh, India Knowledge, care seeking and prevalence of RTI, revealed the prevalence of infection to be 22.7% with the presenting complaint of lower abdominal pain with 37.10% followed by vaginal discharge 31.6%, 40% of the affected women seeked treatment. [ 14 ] In the study conducted among the rural women in Telangana by P. Mani.…”
Section: Discussionmentioning
confidence: 99%
“…Studi tersebut menemukan bahwa pendidikan tinggi merupakan salah satu faktor yang menyebabkan wanita berperilaku baik dalam perilaku pencegahan IMS. 16 Penelitian di Nigeria menyatakan bahwa wanita merupakan kelompok yang masih memiki pemahaman IMS rendah, baik yang sudah maupun belum berpasangan. Mereka menganggap bahwa pencarian informasi dan pengobatan IMS tidak terlalu dibutuhkan karena mereka yakin tidak akan tertular, menganggap IMS sebagai penyakit yang mudah disembuhkan dan merasa tidak perlu untuk melakukan pencegahan IMS di pelayanan kesehatan.…”
Section: Pendahulianunclassified
“…Sejalan dengan penelitian di Mumbai, India tahun 2015 yang menemukan bahwa pendidikan berhubungan dengan perilaku pencegahan IMS (p-value=0,001). 16 Pendidikan tinggi dapat menimbulkan keberanian seseorang dalam mengambil keputusan sehingga dapat berperilaku lebih baik daripada sebelumnya, sebaliknya pendidikan rendah dapat menjadikan pengambilan keputusan seseorang menjadi rendah dan tidak percaya diri, seperti yang ditemukan pada penelitian ini. Penelitian ini menemukan bahwa wanita berpendidikan rendah memiliki risiko 1,134 kali lebih besar untuk berperilaku kurang dalam pencegahan IMS Pendidikan dapat membentuk kesadaran pada diri wanita, mereka memahami akan adanya komplikasi jika infeksi tersebut dibiarkan atau tidak diobati.…”
Section: Pendidikan Terakhirunclassified
See 1 more Smart Citation
“…Previous studies showed that women tend to delay seeking care longer than men and the barriers may be related to individual as well as health system factors [ 19 , 20 ]. Only half in India [ 21 ], and 35% in Ghana [ 22 ] seek care for the sexually transmitted diseases. Based on different studies; delay in seeking care for sexually transmitted diseases were related to high wealth index, presences of offensive odor, perception of symptoms as normal, feeling shay, lack of female health workers, distance to facility, lack of availability of treatments, having non-ulcerative STDs, age, religion, occupational status, and type of family [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%